Prediction of CKD progression and cardiovascular events using albuminuria and pulse wave velocity - Rasmus Kirkeskov Carlsen; Dinah Sherzad Khatir; Danny Jensen; Henrik Birn; Niels Henrik Buus (Karger Publishers, 2023)
Introduction: Chronic kidney disease (CKD) is associated with cardiovascular disease (CVD) and death. Albuminuria is an established risk factor, but additional biomarkers predicting CKD progression or CVD are needed. Arterial stiffness is an easily measurable parameter that has been associated with CVD and mortality. We evaluated the ability of carotid-femoral pulse wave velocity (PWV) and urine albumin-creatinine (UAC) ratio to predict CKD progression, cardiovascular events and mortality in a cohort of CKD patients. Methods: In CKD stage 3-5 patients PWV and UAC were measured at baseline. CKD progression was defined as 50% decline in estimated glomerular filtration rate (eGFR), initiation of dialysis or renal transplantation. A composite endpoint was defined as CKD progression, myocardial infarction, stroke, or death. Endpoints were analyzed using Cox regression analysis adjusted for possible confounders. Results: We included 181 patients (median age 69 [interquartile range 60-75] years, 67% males) with a mean eGFR of 37±12 ml/min/1.73 m2 and UAC 52 [5-472] mg/g. Mean PWV was 10.6 m/s. Median follow-up until first event was 4 [3-6] years with 44 and 89 patients reaching a CKD progression or composite endpoint, respectively. UAC (g/g) significantly predicted both CKD progression (HR 1.5 [1.2;1.8]) and composite endpoints (HR 1.4 [1.1;1.7]) in adjusted Cox regression. In contrast, PWV (m/s) was not associated with neither CKD progression (HR 0.99 [0.84;1.18]) nor the composite endpoint (HR 1.03 [0.92;1.15]). Conclusion: In an ageing CKD population, UAC predicted both CKD progression and a composite endpoint of CKD progression, cardiovascular events, or death, while PWV did not.